The safety and efficacy of applying a high-current temporal interference electrical stimulation in humans - Wang, Yan; Zeng, Ginger Qinghong; Wang, Mengmeng; Zhang, Mingsong; Chang, Chuangchuang; Liu, Qiongwei; Wang, Keqing; Ma, Ru; Wang, Ying; Zhang, Xiaochu (Frontiers in Human Neuroscience, 2024)
BackgroundTemporal interference electrical stimulation (TI) is promise in targeting deep brain regions focally. However, limited electric field intensity challenges its efficacy.ObjectiveThis study aimed to introduce a high-current TI electrical stimulation protocol to enhance its intensity and evaluate its safety and efficacy when applied to the primary motor cortex (M1) in the human brain.MethodsSafety assessments included a battery of biochemical and neuropsychological tests (NSE, MoCA, PPT, VAMS-R, and SAS measurements), 5-min resting-state electroencephalography (EEG) recordings before and after 30-min high-current TI electrical stimulation sessions (20 Hz, 70 Hz, sham). Adverse reactions were also documented post-stimulation. Efficacy evaluations involved two motor tasks, the simple reaction time (SRT) task and the one-increment task, to investigate the distinct contributions of beta (20 Hz) and gamma (70 Hz) oscillations to motor functions.ResultsBiochemical and neuropsychological tests revealed no significant differences between the groups. Additionally, no epileptic activities were detected in the EEG recordings. In the one-increment task, 20 Hz stimulation delayed participants’ reaction time compared to the 70 Hz and sham groups. Conversely, in the SRT task, 70 Hz stimulation exhibited a tendency to enhance participants’ performance relative to the sham group.ConclusionThe proposed high-current TI electrical stimulation is both safe and effective for stimulating the human brain. Moreover, the distinct effects observed in motor tasks underscore the dissociative roles of beta and gamma oscillations in motor functions, offering valuable insights into the potential applications of high-current TI electrical stimulation in brain stimulation research.